KARAKTERISTIK KEWIRAUSAHAAN MAHASISWA UNIVERSITAS JENDERAL SOEDIRMAN (SUATU SURVEI PENDAHULUAN) - Eliada Herwiyanti; Permata Ulfah (Universitas Katolik Indonesia Atma Jaya, 2016)
The purpose of this study was to determine the entrepreneurial characteristics of students in University of Jenderal Soedirman to Entrepreneurship subject. Sampling was done by using a convenience sampling method. Respondents consisted of 55 students from various faculties at the University of Jenderal Sudirman. Data analysis techniques were done by using IBM SPSS 22 software. Final data that can be analyzed is 50 while 5 were excluded from the sample because of data categorized as outliers. The results showed 50 respondents are interested to follow an entrepreneurial course even though 40% of whom there are already into business. Furthermore, result of analysis showed that the greatest reason for the respondents follows entrepreneurship subjects due to desire to develop themselves and to gain extra knowledge. The average respondent have the entrepreneurial characteristics of 83.33%. Surveys show that the most desirable areas of entrepreneurship are fashion, art, and research and development.